Effect of Glycerin Application on Discoloration of Nanofiller Composite in Instant Coffee - Saetikho, Saraswita Gabrillah; Lestari, Sri; Nugroho, Raditya (Indonesian Dental Association, 2022)
Introduction: Most modern society assumes that an attractive appearance is a necessity, including the aesthetics of dental restorations. Nanofiller composite resins are widely used because they can reduce polymerization shrinkage and produce a smooth surface that improves aesthetics. Composite resins can change color due to extrinsic factors such as exposure to exogenous materials, one of which is instant coffee and intrinsic factors such as disruption of the polymerization process. Composite resins can experience polymerization disturbances when their surfaces are exposed to air before being irradiated, thereby disrupting the polymerization process. This is indicated by the formation of an oxygen inhibitor layer (OIL) this layer can reduce the quality of the restoration. This layer cannot be completely removed but the application of glycerin can reduce the formation of the layer. Objectives: To determine the degree of discoloration of nanofiller composite resin coated with glycerin and not due to immersion in instant coffee solution. Methods: The composite resin sample was in the form of a disc with a diameter of 10 mm and a thickness of 2 mm, coated and uncoated with glycerin before irradiation. Samples were immersed in the instant coffee solution for 37 hours and 61 hours. Color changes were observed using the Minolta CR-10 Color Reader. Results: The most obvious color change was in the nanofiller composite resin group that was not coated with glycerin, with an E value of 1.04 with an immersion time of 61 hours. The least color change in the glycerin-coated nanofiller composite resin group, with an E value of 0.91. there was a significant difference in the color changes of the sample group with glycerin and non-glycerin applications. Conclusion: There was color change in the nanofiller composite resin coated with glycerin and non-glycerin. The least color change was in the glycerin-coated group. ABSTRAK Pendahuluan: Sebagian masyarakat modern beranggapan bahwa penampilan yang menarik merupakan suatu kebutuhan, termasuk estetik restorasi gigi. Resin komposit nanofiller banyak digunakan karena dapat mengurangi polymerization shrinkage dan menghasilkan permukaan yang halus sehingga meningkatkan estetik. Resin komposit dapat mengalami perubahan warna akibat faktor ekstrinsik seperti terpapar bahan eksogen salah satunya adalah kopi instan dan faktor intrisik seperti terganggunya proses polimerisasi. Resin komposit dapat mengalami gangguan polimerisasi ketika permukaannya terpapar udara sebelum disinar, sehingga menyebabkan terganggunya proses polimerisasi. Hal ini ditandai dengan terbentuknya lapisan oxygen inhibitor layer (OIL) lapisan ini dapat mengurangi kualitas restorasi. Lapisan ini tidak dapat sepenuhnya dihilangkan tetapi aplikasi gliserin dapat mengurangi pembentukan lapisan tersebut. Tujuan: Mengetahui tingkat perubahan warna resin komposit nanofiller dengan dan non gliserin akibat perendaman larutan kopi instan. Metode: Sampel resin komposit berbentuk cakram diameter 10 mm tebal 2 mm, dengan dan non gliserin sebelum disinar. Sampel direndam dalam larutan kopi instan selama 37 jam dan 61 jam. Perubahan warna diamati dengan menggunakan alat Color Reader Minolta CR-10. Hasil: Perubahan warna terbesar pada kelompok resin komposit nanofiller non gliserin, dengan nilai ΔE 1,04 dengan waktu perendaman 61 jam. Perubahan warna terkecil pada kelompok resin komposit nanofiller yang dilapisi gliserin, dengan nilai ΔE 0,91 dengan waktu perendaman 61 jam. Terdapat perbedaan bermakna pada kelompok sampel dengan dan non gliserin. Kesimpulan: Terjadi perubahan warna pada resin komposit nanofiller yang dilapisi gliserin dan non gliserin. Perubahan warna yang terkecil terjadi pada kelompok yang dilapisi gliserin.